Harassment and Mental Distress Among Adolescent Female Students by Sexual Identity and BMI or Perceived Weight Status. Issue 8 (11th May 2017) - Johns, Michelle Marie; Lowry, Richard; Demissie, Zewditu; Robin, Leah
Abstract : Objective: Sexual minority girls (lesbian/bisexual) and girls with overweight/obesity experience high rates of discrimination and mental distress. This study explored whether BMI or perceived weight status might compound sexual minority girls' risk for harassment and mental distress. Methods: Data on female students from the national 2015 Youth Risk Behavior Survey ( n  = 7, 006) were analyzed. Logistic regression was used to examine differences in bullying, harassment, and mental distress across sexual identity/BMI groups: heterosexual/normal‐weight, heterosexual/overweight, sexual minority/normal‐weight, and sexual minority/overweight. Procedures were repeated with four analogous groups created from sexual identity and perceived weight. Results: Across sexual identity/BMI groups, being overweight increased heterosexual females' odds of being bullied or experiencing suicidal thoughts and behaviors. Regardless of weight status, sexual minority females had greater odds for each outcome than heterosexual females. Sexual minority females who perceived themselves as overweight had greater odds of suicidality than all other sexual minority/perceived weight groups. Conclusions: Double jeopardy may exist for sexual minority female students who perceive themselves as overweight. Professional development with school staff on how to create a positive climate for sexual minorities and those with overweight/obesity and addressing positive identity and body image within school‐based suicide prevention efforts may be important to the well‐being of adolescent girls.